How to forage for mushrooms without dying : an absolute beginner's guide to identifying 29 wild, edible mushrooms - Hyman, Frank (Storey Publishing, 2021)
"This is the book for anyone who walks in the woods and would like to learn how to identify just the 29 edible mushrooms they're likely to come across. With Frank Hyman's . . . guidelines, readers will be confident in identifying which mushrooms they can safely eat and which ones they should definitely avoid"--Provided by publisher.